Potensi Ekstrak Daun Afrika (Vernonia amygdalina), Daun Pepaya (Carica papaya L) Serta Kombinasi Kedua Ekstrak Terhadap Jumlah Folikel Primer, Sekunder dan Tersier Pada Mencit (Mus musculus) - Sukarjati Sukarjati; Ganda Adi Nugroho (LPPM Universitas PGRI Adi Buana Surabaya, 2021)
African leaf (Vernonia amygdalina) and papaya leaf (Carica papaya L) are plants that contain secondary metabolites and are thought to have antifertility effects. V amygdalina and C papaya L leaves contain flavonoids, saponins, tannins, and alkaloids. The purpose of this study was to prove that V amygdalina leaf extract, C papaya L leaf and the combination of the two extracts could reduce the number of primary, secondary and tertiary follicles. This study used 44 female mice. Extraction was carried out by maceration . The doses of V amygdalina leaf extract and C papaya L leaf extract used were 150 mg/kg BW, 200 mg/kg. kg BW, 250 mg/kg BW and the combined doses of V amygdalina leaf extract and C papaya leaf were 75:75 mg/kg BW, 100:100 mg/kg BW, and 125:125 mg/kg BW. The positive control used KB Andalan with a dose of 0.000078 mg. Ovarian histology was made according to laboratory standards Data were analyzed using One-Way ANOVA tand LSD test. The results showed that the administration of V amygdalina leaf extract, C papaya leaf, and their combination significantly affected the decrease in the number of primary follicles (P= 0.03), secondary follicles (P=0.032) and tertiary follicles (P=0.033). The combination extract of V amygdalina leaf and C papaya leaf at a dose of 125:125 mg/kg BW has the most potential as a natural contraceptive ingredient.